Recent advances in critical materials for quantum dot-sensitized solar cells: a review. Issue 34 (14th September 2015) - Duan, Jialong; Zhang, Huihui; Tang, Qunwei; He, Benlin; Yu, Liangmin
<x xml:space="preserve">Abstract</x> Quantum dot-sensitized solar cells (QDSCs) present promising cost-effective alternatives to conventional silicon solar cells due to their distinctive properties such as simplicity in fabrication, possibility to realize light absorption in wide solar spectrum regions, and theoretical conversion efficiency up to 44%.